Density Functional Theoretical and Time‐dependent Density Functional Theoretical Study on Thiophene–Benzothiadiazole‐based Polymers. (January 2015) - Woo, Han Young; Uddin, Mohammad Afsar; Hwang, Sungu
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10069-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>